City profile: New Tehri. (July 2020) - Kaur, Harsimran; Garg, Pushplata
Abstract: Large-scale development projects often lead to massive population displacement induced by the Dam. A number of planners, responsible organizations, resettlement experts and academic researchers have all put forward proposals for resettlement of such displaced population. Such an example of resettlement is the development of New Tehri Township for the people displaced by the Tehri Dam in India. New Tehri is an egalitarian city designed to achieve functionality, environmental sustainability, deep sensitivity of people, and their concerns. Planning for the new town entailed the integration of several diverse and sensitive issues like a high sense of responsiveness to people's needs; respect for the holding capacity and natural systems of the land; sustainability of the environment, and equal opportunities for all. In order to achieve the goal, five primary criteria, combined to form the basis for overall design and planning. The article examines the elements of urban form identified with reference to the primary criteria developed by the planners of the township and explains their assessment in the case study selected. The article attempts to highlight opportunities for researchers and planners in India and the world for analyzing, evaluating and criticizing hillside urban development and resettlement projects in terms of their sustainability. Highlights: New Tehri Town is an example of development-induced resettlement for displaced people by the Tehri dam construction in India. Regional setting in context of unique physiography, settlement evolution, socio-economic profile, environmental characteristics, urban form and pattern are discussed. Highlight opportunities for researchers and planners by setting an example of sustainable hillside development in India and the world.